The technology of medications. Issues of pharmaceutical manufacturing : Manual to practical classes in for pharmaceutical students 4-d year study specialty 226 “Pharmacy” - Burlaka, B. S.; Gladyshev, V. V.; Nagorniy, V. V.; Puchkan, L. O.; Gladysheva, S. A.; Бурлака, Богдан Сергійович; Гладишев, Віталій Валентинович; Нагорний, Володимир Володимирович; Пучкан, Любов Олександрівна; Гладишева, Світлана Анатоліївна (Запорізький державний медико-фармацевтичний університет, 2024)
Based on the requirements of the Technology of Medications Work Program, this book presents the main theoretical issues and provides practical tasks for compounding of medicines – Maximum purified preparations, tablets, injectable solutions capsules etc. The book contributes to the students comprehension and visualization of Pharmaceutical Compounding and designed in a clear scheme. Заснований на вимогах робочої програми з технології ліків, цей посібник представляє основні теоретичні питання та практичні завдання стосовно промислового виготовлення максимально-очищених препаратів, таблеток, ін’єкційних засобів, капсул. Складений за прозорою схемою, посібник сприяє розумінню та уявленню студентами промислового виготовлення ліків.